Propriedades estruturais, eletrônicas e vibracionais das cerâmicas FE2WO6 E SRCUSI4O10 - SILVA, Hilton Beserra da (2024)
In this research, the polycrystalline ceramics Fe2WO6 and SrCuSi4O10 were synthesized and characterized. The iron tungstate (Fe2WO6) ceramic was synthesized in powder form by solid- state reaction. Initially, the sample was studied under ambient conditions (300 K) using X-ray diffraction and Raman spectroscopy techniques. Furthermore, density functional theory (DFT) was applied to determine the Raman vibrational modes, aiming to understand and elucidate the vibrational, structural, and electronic properties of the crystal under ambient conditions. Subsequently, a study of the vibrational and structural properties under varying pressure and temperature was conducted using Raman spectroscopy. The experimental measurements of Raman spectroscopy under high pressures were performed in the range of 0.0–7.0 GPa and at low temperatures between 300–10 K. The results showed that the Fe2WO6 crystal is stable for the pressure and temperature values studied. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) were used to evaluate the pressure and temperature ranges conducive to conformational transformations in the Fe2WO6 crystal phase. The polycrystalline ceramic SrCuSi4O10 was synthesized in a similar manner through solid-state reaction. The sample was characterized by powder X-ray diffraction (XRPD), Raman spectroscopy, Fourier- transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), lattice dynamic calculations, and electronic property analyses. X-ray analysis showed that the crystal structure of the ceramic belongs to the tetragonal system with the P4/ncc space group and four formula units per unit cell (Z = 4). The SEM micrographs showed a morphology of layered microplates, with some irregularity in size and shape. Regarding vibrational properties, the theoretical calculation was performed using a rigid-ion model to assign the experimental Raman and IR modes. Additionally, electronic property calculations were conducted using Density Functional Theory (DFT).